Extractables and leachables from poly-ε-caprolactone/phosphate based glass composites - Brown, Helen C. (N/A, 2016)
In this study poly-ε-caprolactone and iron containing phosphate based glass composites have been investigated in terms of their degradability, structural changes and potential for fracture fixation devices. Any material being used within the body requires Regulary acceptance. A key aspect of this is safety and a toxicological assessment of any extracted or leached species. As a crucial part of the project, PBG fibres were assessed for extractables and leachables. Weight loss was also investigated in order to assess the durability with increasing iron content. The following glass fibre compositions were studied: 50P45Ca5Na, 50P35Ca5Na5Fe and 50P30Ca5Na10Fe. They were then fabricated into composites, with PCL, by compression moulding and stored in pH4 and pH7 buffer, krebs solution, saline solution and water for 78 weeks at 37oC. The resulting composites, and their corresponding solutions, were assessed for extractables and leachables, weight change, pH shifts, porosity and pore size, thermal properties and structural changes.